Research on the Path of Criminal Law Regulation for the Protection of Data Legal Interests - Liu, Qingyuan; Sun, Chen (International Journal of Social Sciences and Public Administration, 2024)
In the face of the emerging new types of crimes in the digital economy era, criminal law, as a fallback link in the legal regulatory system, should respond accordingly. Therefore, the weakening of the principle of legality of crimes and punishments brought about by the operation of the digital economy should not be understood as an absolute negative value, and should be re examined in conjunction with the logic of digital economy operation. At present, the regulation of data itself in China’s criminal law is still limited to the carrier and material entity of data - traditional computer information systems. The recognition of data legal interests still remains at the level of the actual legal interests reflected behind the data (such as property and personality legal interests). In the current situation where various legal interests may be reflected in the data, it is necessary to strengthen the overall attention to the data itself and promote targeted legislation for the protection of data legal interests. Only then can the digital economy achieve significant and healthy development under the protection of the "last line of defense" criminal law, while also being more in line with the concept of "strict but not severe" criminal law.